Relationship between student learning interest and mathematics learning achievement: A meta-analysis - Ili, La; Rumasoreng, Muhammad Irfan; Prabowo, Anggit; Setiana, Dafid Slamet; Latuconsina, Adam (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
Mathematics is regarded as one of the most important lessons that any student must learn. Internal and external factors, in general, influence students' mathematics learning achievement. One of the internal factor variables is students’ learning interest in mathematics. Many research publications show that the variable of interest is strongly related to mathematics learning achievement, so this study aims to prove and quantify the size of the relationship between mathematics learning interest and mathematics learning achievement using quantitative meta-analysis research approaches. The independent variable is student learning interest, and the dependent variable is mathematical learning achievement. The data was acquired from an online database search on Google Scholar within the 2009 to 2019 timeframe. Thirty research publications that satisfied the required criteria were utilized as the sample. Data analysis uses a quantitative meta-analysis approach with a correlation meta-analysis. The findings revealed a favorable and substantial (5% significance level) link between learning interest and student mathematics learning achievement. The average weight value of effect size was 0.540 in the range of 0.430 to 0.640 in the medium category. These findings have demonstrated the consistency of previous researchers' conclusions.